The Associations Between Parental Playfulness, Parenting Styles, the Coparenting Relationship and Child Playfulness - Harshita Seal; Jean-François Bureau; Audrey-Ann Deneault (Behavioral Sciences, 2025)
This study explores the associations between parental playfulness and various aspects of parenting, specifically role overload, parenting behaviors, and the quality of coparenting. In addition, we explore the relation between parental playfulness and child playfulness, as well as the differences in playfulness between mothers and fathers. This cross-sectional, questionnaire-based study relied on a sample of 348 parents (84.7% mothers) of children aged 3–8 years old (52.9% girls). Significant associations were found between parental playfulness and cognitive aspects of child playfulness (e.g., sense of humor). Certain dimensions of coparenting (e.g., support) and other parenting behaviors (e.g., challenging and warmth) were also correlated with parental playfulness. There was no association found between parental playfulness and parental role overload. However, a significant moderation effect of parental gender was found only for the association between parental playfulness and role overload. This analysis showed that parental playfulness was positively associated with role overload for fathers but was negatively associated for mothers. Lastly, we did not identify differences between mothers’ and fathers’ self-reported playfulness. These results provide important information about an understudied parental behavior, which may inform interventions promoting positive parenting.